A review on progress in research on biomarkers of frailty in elderly - Jinzhu YANG; Lingxiao HE; Ya FANG (Editorial Office of Chinese Journal of Public Health, 2023)
Frailty is a common clinical condition in older adults, which is characterized by decreased steady-state reserve capacity and anti-stress ability. The incidence of frailty is high in China and is associated with many adverse outcomes, bringing heavy burden to the family and society. Therefore, frailty monitoring and early detection will contribute to the implementation of relevant interventions and to delay the onset of frailty or even reverse frailty status and finally to a good maintenance in health condition. Since frailty is the result of multi-organ functional declines, evaluations on biological factors related to body function may provide a new solution for frailty monitoring. In this paper, we summarize the research on frailty-related biomarkers of metabolism, immunity, oxidative stress, inflammation and nutrition for providing a reference to monitoring and early diagnosis of frailty.